2021
DOI: 10.1186/s40729-021-00302-5
|View full text |Cite
|
Sign up to set email alerts
|

Patient’s perception of recovery after osteotome-mediated sinus floor elevation with Bio-Oss collagen compared with no grafting material: a randomized single-blinded controlled trial

Abstract: Background Osteotome-mediated sinus floor elevation with or without a grafting material is associated with high implant survival, intrasinus bone gain, and low frequency of complications. However, patient’s perception of recovery and satisfaction with the surgical intervention are rarely reported. The objective of the present randomized controlled trial was to assess patient’s perception of recovery after osteotome-mediated sinus floor elevation with Bio-Oss collagen compared with no grafting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 22 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…However, specific scores related to number of days with pain, eating difficulties, and sleep disturbances were significantly increased in the graft group. 56 Contrasting findings were reported for the adjunctive effect of the graft on vertical endo-sinus bone gain. Whereas one study reported greater bone gain and higher proportions of implants completely embedded in a radiopaque area for the graft group 53 even at longer follow-up intervals, 57,58 another study 54 or its follow-up 59 failed to find a significant adjunctive effect of the graft.…”
Section: May the Number Of Surgical Sessions And Chair Time Be Reduce...mentioning
confidence: 93%
See 4 more Smart Citations
“…However, specific scores related to number of days with pain, eating difficulties, and sleep disturbances were significantly increased in the graft group. 56 Contrasting findings were reported for the adjunctive effect of the graft on vertical endo-sinus bone gain. Whereas one study reported greater bone gain and higher proportions of implants completely embedded in a radiopaque area for the graft group 53 even at longer follow-up intervals, 57,58 another study 54 or its follow-up 59 failed to find a significant adjunctive effect of the graft.…”
Section: May the Number Of Surgical Sessions And Chair Time Be Reduce...mentioning
confidence: 93%
“…Two studies showed a tendency to higher incidence in the graft group, 52,54 whereas membrane perforation occurred only in the graftless group in the remaining study. 56 In general, biological complications manifested with low incidence rates irrespective of the adjunctive use of a graft, and peri-implantitis leading to implant loss (when occurred) was limited to one case per treatment arm. No evident differences were found in the incidence of biological complications or implant loss due to peri-implantitis in the studies available.…”
Section: May the Number Of Surgical Sessions And Chair Time Be Reduce...mentioning
confidence: 95%
See 3 more Smart Citations